Product liability in Malaysia - Amin, Naemah (Sweet & Maxwell Asia, 2007)
The march of modernisation and the introduction of products of greater sophistication and complexity in the marketplace have also seen the rising trend of damage, injury and adverse consequences suffered by consumers as a result of product failure, shoddy workmanship or defective design. Product liability law seeks to provide redress for damage suffered by the victims of defective products. The body of law encompasses a composite mix of various statutes and common law principles.